The district “Dyrekcja” in Chełm – the evaluation of district after 80 years of its foundation - Szmygin, Bogusław; Trochonowicz, Maciej (Budownictwo i Architektura / Civil and Architectural Engineering, 2010)
District “Dyrekcja” built in the year 1928-1939 was regarded the second after the Gdynia largest investment of the period between world wars due to its size number of houses. The district represents the whole set of the values resulting the ideological programme (national symbolism), spatial composition, coherent architectural form of the buildings and their technical characteristics. The presented article is aimed as a complex evaluation of the district “Dyrekcja” after 80 years of its foundation.